Flexible and unbureaucratic democracy promotion by the EU? The European Endowment for Democracy between wishful thinking and reality - Julia Leininger; Solveig Richter (Stiftung Wissenschaft und Politik (SWP), 2012)
In June 2012 the EU set up the European Endowment for Democracy (EED) with the aim of supporting pro-democracy actors predominantly in the European Neighbourhood and of doing so quickly, flexibly, unbureaucratically and audaciously. But wishful thinking and reality are still separated by a wide gap: first, it is doubtful that the Endowment can be sure of stable, long-term financing. While showing little willingness to support the Endowment, the EU Member States nonetheless want a right to a say in how it is run. Second, what the EU is seeking to achieve with the EED, actor-centred democracy promotion in complex situations of radical change, is a highly risky venture. Third, it is unclear how the EED is to complement existing EU instruments with similar tasks. To ensure that it has a positive impact, the Endowment should have the EU Member States' financial and political backing. It is also important for the EED to avoid duplication and develop a long-term strategy with other democracy promoters in the countries in which it operates
Keywords: 320